Nexus between farmland transfer, agricultural loans, and grain production: empirical evidence from China - Ding, Zhao; Zhang, Qianyu; Tang, Yu (Frontiers in Sustainable Food Systems, 2024)
Food production is an urgent global concern. This study utilized provincial-level data from China and employed a two-way fixed effects model and instrumental variable approach to empirically investigate the interplay between farmland transfer, agricultural loans, and grain production in China. The findings underscore a noteworthy positive correlation between farmland transfer and grain production. Conversely, agricultural loans exhibit a significantly negative impact on grain production. However, the positive interaction term between farmland transfer and agricultural loans suggests that while profit-driven financial activities may not inherently favor grain production, they facilitate more efficient utilization of farmland resources, ultimately promoting grain production. These results emphasize the importance of the government's continued support for rural land system reform and active guidance of farmland transfer.Moderate-scale operation of farmland is a prerequisite for finance to play a lubricating and catalytic role. In addition, it is necessary to guide agricultural finance to invest in medium and long-term projects of agricultural production and to prevent the potential food crisis caused by the phenomenon of "non-farming" of agricultural loans.